Strategi Pemasaran Batik Lamongan dan Kontribusinya terhadap Perekonomian Lokal - Warsono, Heribertus Yudho (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This study aims to identify and analyze the marketing strategies employed by the Lamongan batik industry and to evaluate its contribution to the local economy. As a traditional Indonesian cultural product, Lamongan batik holds significant aesthetic and economic potential that can be developed through effective marketing strategies. This qualitative descriptive research uses a case study method, incorporating in-depth interviews with industry players, marketers, and direct observations of marketing practices. The findings reveal that successful marketing strategies for Lamongan batik involve a combination of traditional promotion and digital platform utilization, which has effectively increased awareness and demand at local and national levels. Furthermore, the economic contribution of Lamongan batik to the local economy is evident through job creation, growth of small businesses, and increased household income. This research provides insights for developing marketing strategies for cultural products and supports government policies to promote creative economies in regional areas.